Continuously-prepared aluminum-zinc alloy for air battery and air battery
By using low-temperature molten salt electrolyte and constant current electrolysis method in air batteries, the problems of self-corrosion and passivation of the anode in air batteries are solved, and the service life and power density of the battery are improved.
Patent Information
- Application Number
- CN202411623525.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
In existing air batteries, when metal aluminum and metal zinc are used as anodes, self-corrosion reactions and passivation of electrode activity are prone to occur, which limits its development.
Low-temperature molten salt electrolyte is used, and metal aluminum tape or metal zinc tape is used as electrodes to regulate the plating current and transmission rate under a protective atmosphere to achieve continuous preparation of aluminum-zinc alloys.
It improves the service life and power density of air batteries, realizes the uniform coating and dense structure of aluminum-zinc alloy, and enhances its corrosion resistance.
Smart Images

Figure CN119465309A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy material preparation, and relates to a continuously prepared aluminum-zinc alloy for air batteries and an air battery. Background Art
[0002] Air batteries use active metals as anode active materials and oxygen in the air as cathode active materials. Oxygen passes through the gas diffusion electrode to the gas-liquid-solid three-phase interface and reacts with the metal anode to release electrical energy. It has the advantages of high specific energy, stable discharge voltage, low cost, non-toxicity, low pollution, and simple structure. It is considered to be a sustainable energy source with great development and application prospects in the future.
[0003] Metallic aluminum and metallic zinc have shown great potential when used as anodes in air batteries because of their significant specific energy. Zinc-air batteries usually use metallic zinc as the anode, oxygen as the cathode, and potassium hydroxide aqueous solution as the electrolyte solution. The reaction principle is: Zn+1 / 2O2→ZnO. Since zinc is thermodynamically unstable in alkaline solutions, a small amount of hydrogen evolution corrosion reaction will occur when zinc is discharged in alkaline electrolytes, resulting in the self-corrosion problem of the zinc electrode, which restricts its large-scale commercial application. Aluminum-air batteries are usually air batteries composed of aluminum or aluminum alloy as the anode, air as the cathode, and neutral or alkaline aqueous solution as the electrolyte. The principle of its electrochemical reaction is: 4Al+3O2+6H2O+4OH under alkaline conditions. - →4 Al(OH)4 - , 4Al+3O2+6H2O→4 Al(OH)3 under neutral conditions. At present, the battery still faces some problems that need to be solved. The presence of a passivation film on the surface of the metal aluminum will inhibit the electron loss oxidation reaction of aluminum, resulting in an increase in the aluminum electrode potential and a decrease in the battery voltage. In addition, the aluminum anode will undergo a self-corrosion reaction in the alkaline electrolyte, namely the hydrogen evolution reaction, which will cause serious self-corrosion discharge of the battery on the one hand, and produce a large amount of flammable hydrogen on the other hand.
[0004] It can be seen that when metallic aluminum or metallic zinc is used as the anode alone, serious self-corrosion reactions will occur, and insoluble by-products will also be generated on its surface, thereby passivating the electrode activity, which limits the development of aluminum-air batteries and zinc-air batteries.
[0005] Chinese invention patent CN105112963B provides a method for preparing metallic aluminum and its alloys by molten salt electrodeposition. The use of amide aluminum molten salt as the medium for electrodeposition of aluminum and its alloys allows the electrolysis process to be carried out at room temperature, saving energy while reducing the corrosion of the electrolyte to the equipment; and the yield of metallic aluminum reaches 99%; in addition, the molten salt price of the invention scheme preparation process is relatively cheap and the eutectic temperature is low, which can improve the yield of metallic aluminum and reduce production costs compared with the existing preparation process of aluminum and its alloys. The molten salt electrolyte in this patent contains amide compounds, and by adding magnesium salts, titanium salts or manganese salts thereto, aluminum-magnesium alloys, aluminum-titanium alloys and aluminum-manganese alloys can be finally obtained. However, this invention is not for aluminum metal modification for air batteries, and cannot be used for the preparation of aluminum-zinc alloys.
[0006] Chinese invention patent application CN101914706A discloses a zinc-aluminum-neodymium alloy and a molten salt electrolysis preparation method thereof, wherein a molten salt system with a mass ratio of LiCl: KCl: AlF3 = 45%: 45%: 10% is heated to 450°C in an electrolytic furnace, and then a mixture of Nd2O3 and ZnCl2 with a mass ratio of 1:5 is added. Metal molybdenum is used as the cathode and graphite is used as the anode. The sinking cathode method is adopted, the electrode distance is 5 cm, the electrolysis temperature is 450-480°C, and the cathode current density is 6.4A / cm 2 ~12.7A / cm 2 , anode current density 0.5A / cm 2 , the cell voltage is 6.4 ~ 10.2V, after 120 minutes of electrolytic deposition, it is kept at 800℃ for 2h, and a liquid Zn-Al-Nd alloy is obtained near the cathode in the molten salt electrolytic cell. After solidification, a solid alloy is obtained. In this application, the electrolyte temperature exceeds 400℃, and it needs to be kept at 800℃ after electrodeposition. The energy consumption of the preparation process is too high, and the production cost is too high.
[0007] Traditional zinc-aluminum alloy manufacturing methods include a cross-blending method. Chinese invention patent CN 1258755A provides a zinc-aluminum alloy preparation process. The technical solution is characterized in that molten aluminum liquid is first poured into molten zinc liquid, or block aluminum is added to molten zinc liquid, and the temperature is increased to melt and fully stirred to obtain zinc-aluminum alloy. The cross-blending method has relatively simple equipment, but has a series of problems such as long process, high energy consumption, large metal loss, and serious environmental pollution.
[0008] The above existing technologies are not for aluminum metal modification for air batteries, and cannot be used for the preparation of aluminum-zinc alloys. Based on the above problems, it is particularly important to modify aluminum or zinc metal in a process with low energy consumption, continuity, and ease of industrial production. At the same time, the modified metal anode can be used in air batteries to greatly improve the service life and power density of metal-air batteries. Summary of the invention
[0009] Based on this, the purpose of the present invention is to provide a continuous preparation of aluminum-zinc alloy for air batteries and a preparation method, using metal aluminum strip or metal zinc strip as an electrode, and adopting a constant current electrolysis method in a low-temperature molten salt electrolyte to achieve its continuous preparation process to meet the needs of large-scale industrial production.
[0010] The invention also provides application of the alloy in an air battery and an air battery.
[0011] To achieve the above object, the present invention adopts the following technical solutions: A continuously prepared aluminum-zinc alloy for air batteries is prepared by using a metal zinc rod as an anode and a metal aluminum strip as a cathode or a metal aluminum rod as an anode and a metal zinc strip as a cathode in an electrolyte, and regulating the electroplating current and the transmission rate of the metal aluminum strip or the metal zinc strip in a protective atmosphere; the electrolyte is mainly composed of molten aluminum chloride and zinc chloride. Further, the electrolyte also includes auxiliary components, and the auxiliary components include any one or more of molten lithium chloride, potassium chloride and sodium chloride; the molar ratio of the sum of the molar amounts of aluminum chloride and zinc chloride to the auxiliary components is 3-5:0-1.
[0012] Furthermore, the electroplating current density is >1 mA / cm 2 The preferred electroplating current density is 1~20 mA / cm 2 The more preferred plating density is 60~120 mA / cm 2 .
[0013] Furthermore, the transmission rate is greater than 15 cm / h, and the preferred transmission rate is 15-30 cm / h.
[0014] Furthermore, the temperature of the electrolyte is ≥150°C, preferably 150-200°C.
[0015] Furthermore, a polymer is compounded on the surface of the metal aluminum strip or the metal zinc strip to achieve control of the electroplating position, and the polymer can be an insulating polymer.
[0016] Furthermore, the electroplating current is positively correlated with the transmission speed.
[0017] In the preparation method provided by the present invention, the transmission rate is related to the electroplating current density. By adjusting the electroplating current density and the transmission rate, a uniform alloy coating is finally obtained. During electroplating, the temperature of the molten salt electrolyte is maintained at ≥150°C to obtain an electroplating solution with good fluidity; the electroplating time is positively correlated with the size and rotation time of the alloy metal strip to be prepared. This method can realize a continuous preparation process and realize electroplating on both sides of the metal strip at the same time. Single-sided electroplating can also be achieved by compounding a polymer on one side of the metal strip, or compounding a polymer at any position on the metal strip to leave a part that needs to be electroplated, so as to realize electroplating of different parts.
[0018] The present invention also provides an application of an aluminum-zinc alloy for an air battery as an anode in an air battery.
[0019] The present invention further provides an air battery, the anode of which is the continuously prepared aluminum-zinc alloy for air batteries provided by the present invention.
[0020] Finally, the present invention provides a method for continuously preparing aluminum-zinc alloy for air batteries. In an electrolyte, a metal zinc rod is used as an anode and a metal aluminum strip is used as a cathode, or a metal aluminum rod is used as an anode and a metal zinc strip is used as a cathode. In a protective atmosphere environment, the electroplating current and the transmission speed of the metal aluminum strip or the metal zinc strip are regulated to continuously prepare the alloy. The electrolyte is mainly composed of molten aluminum chloride and zinc chloride.
[0021] The beneficial effects of the present invention are: 1. The air battery provided by the present invention uses a continuously prepared aluminum-zinc alloy as an anode material, thereby improving service life and power density.
[0022] 2. The continuously prepared aluminum-zinc alloy for air batteries provided by the present invention uses a metal aluminum strip or a metal zinc strip as an electrode and is used for the first time in a molten salt system with low temperature and low energy consumption. By controlling the transmission speed of the metal strip, a continuous preparation process can be achieved to meet the needs of large-scale industrial production.
[0023] 3. The continuously prepared aluminum-zinc alloy for air batteries provided by the present invention adopts a constant current electrolysis method and realizes in-situ and quantitative alloying of metal aluminum / metal zinc by controlling the electroplating current and electroplating time.
[0024] The aluminum-zinc alloy prepared by the method provided by the present invention has a macroscopically smooth surface of the alloy layer, a dense microstructure, and excellent corrosion resistance, and can be widely used as an anode material in air batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Attached Figure 1 The SEM image of the metal surface morphology in Example 1, wherein a is the original metal aluminum, and b is the aluminum-zinc alloy layer after electrogalvanizing; Attached Figure 2 This is a SEM image of the metal surface morphology in Example 4, where a is the original metal zinc and b is the aluminum-zinc alloy layer after aluminum electroplating; Attached Figure 3 The XRD spectrum of the phase structure of the zinc-aluminum alloy in Example 1; Attached Figure 4 The XRD spectrum of the phase structure of the aluminum-zinc alloy in Example 4; Attached Figure 5 This is a test diagram of the corrosion resistance of the aluminum-zinc alloy in Example 1; Attached Figure 6 This is a performance test diagram of the aluminum-zinc alloy used in aluminum-air battery in Example 1; Attached Figure 7 This is a performance test diagram of the aluminum-zinc alloy used in zinc-air battery in Example 4; Attached Figure 8 Schematic diagram of the continuous preparation process of aluminum-zinc alloy for air batteries, wherein 1 is an electrolytic cell, 2 is a rotating shaft, 3 is a metal zinc rod / metal aluminum rod, and 4 is a metal aluminum strip / metal zinc strip. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. The embodiments mentioned are all implemented on the premise of the technical solutions of the present invention, and detailed implementation processes are given, but it should be stated that the protection scope of the present invention is not limited to the following embodiments.
[0028] The present invention provides a continuous preparation of aluminum-zinc alloy for air batteries and a preparation method thereof. In a molten salt electrolyte containing aluminum ions and zinc ions, when an external power supply is connected, the anode dissolves and an alloy phase is formed at the cathode. The reaction equation is: Zn + Al = Al x Zn y .
[0029] When the aluminum strip is used as the cathode and the zinc rod is used as the anode, reduction reaction and alloying reaction occur at the cathode, that is, the zinc ions in the electrolyte are reduced by electrons and then alloyed with the aluminum substrate in situ. The corresponding chemical reaction equations are Zn2+ +2e - = Zn; Zn + Al = Al x Zn y ; Oxidation reaction occurs at the anode, and the chemical reaction equation is: Zn - 2e - = Zn 2+ .
[0030] When the metal zinc strip is used as the cathode and the metal aluminum rod is used as the anode, reduction reaction and alloying reaction occur at the cathode, that is, the aluminum ions in the electrolyte are reduced by electrons, and then form an alloy with the zinc bottom in situ. The corresponding chemical reaction equations are Al 3+ +3e - = Al; Zn + Al = Al x Zn y ; Oxidation reaction occurs at the anode, and the chemical reaction equation is: Al - 3e - =Al 3+ .
[0031] The metal aluminum strip (rod) and metal zinc strip (rod) used in the present invention are both industrial grade with a purity of >99.5%. The size of the aluminum strip and the zinc strip can be flexibly selected according to the size of the electrolytic cell and the production output requirements in actual production. In the preparation process, if the metal strip is metal aluminum, the metal rod is a zinc rod, and vice versa, if the metal strip is metal zinc, the metal rod is an aluminum rod. The present invention is pioneering in using a molten salt electrolyte containing aluminum chloride and zinc chloride in the process of preparing aluminum-zinc alloy. The melting point of the molten salt can reach as low as 120°C and has good fluidity.
[0032] The process of continuously preparing aluminum-zinc alloy for air battery of the present invention is as follows Figure 8 As shown, in a protective atmosphere, an electrolytic cell 1 with a rotating shaft 2 is prepared, the prepared molten salt electrolyte is added to the electrolytic cell 1, the metal zinc rod / metal aluminum rod 3 is used as the anode, the metal aluminum strip / metal zinc strip 4 is used as the cathode, the electrochemical workstation power is turned on, the current is applied, the transmission speed of the rotating shaft 2 is set, and the electroplating time is controlled according to the length of the metal strip to continuously prepare the aluminum-zinc alloy for air batteries. The prepared aluminum-zinc alloy for air batteries is tested for morphology and metallographic structure, and corrosion resistance, and is assembled as an anode to obtain an air battery, and the battery performance is tested.
[0033] Example 1 Electrolyte: composed of aluminum chloride, zinc chloride and lithium chloride in a molar ratio of 3:1:1. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal zinc rod, and the cathode is a metal aluminum strip. The total length of the aluminum strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 80 mA / cm 2 , the transmission speed is 15cm / h.
[0034] Example 2 Electrolyte: composed of aluminum chloride, zinc chloride and potassium chloride in a molar ratio of 2:2:1. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal zinc rod, and the cathode is a metal aluminum strip. The total length of the aluminum strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 100mA / cm 2 , the transmission speed is 20m / h.
[0035] Example 3 Electrolyte: composed of aluminum chloride, zinc chloride, lithium chloride and sodium chloride in a molar ratio of 3:1:0.5:0.5. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal zinc rod, and the cathode is a metal aluminum strip. The total length of the aluminum strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 80 mA / cm 2 , the transmission speed is 15cm / h.
[0036] Example 4 Electrolyte: composed of aluminum chloride, zinc chloride and lithium chloride in a molar ratio of 1:3:1. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal aluminum rod, and the cathode is a metal zinc strip. The total length of the zinc strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 100 mA / cm 2 , the transmission speed is 20cm / h.
[0037] Example 5 Electrolyte: composed of aluminum chloride, zinc chloride, lithium chloride and potassium chloride in a molar ratio of 2:2:0.6:0.4. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal aluminum rod, and the cathode is a metal zinc strip. The total length of the zinc strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 80 mA / cm 2 , the transmission speed is 15cm / h.
[0038] Example 6 Electrolyte: It is composed of aluminum chloride, zinc chloride and sodium chloride in a molar ratio of 2:2:1. After melting, the electrolyte temperature is controlled to 150°C; Electrode: The anode is a metal aluminum rod, and the cathode is a metal zinc strip. The total length of the zinc strip is 1m, and the dimensions immersed in the electrolyte are: width 3cm, length 5cm, thickness 0.3cm; Electroplating conditions: current density 100 mA / cm 2 , the transmission speed is 20cm / h.
[0039] Implementation effect analysis: 1. Morphology test The surface morphology and phase structure of the prepared aluminum-zinc alloy were tested by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. Figure 1-4 shown.
[0040] Figure 1 This is a SEM image of the metal surface morphology in Example 1, wherein a is the original metal aluminum and b is the aluminum-zinc alloy layer after electrogalvanizing. Figure 2 The SEM image of the metal surface morphology in Example 4, wherein a is the original metal zinc and b is the aluminum-zinc alloy layer after electroplating with aluminum. It can be seen from the figure that the preparation method provided by the present invention realizes the dissolution of metal zinc and forms a porous alloy phase with metal aluminum at the cathode, and the surface of the layer is flat at the macroscopic level and the microscopic structure is dense.
[0041] Figure 3 : This is the XRD spectrum of the zinc-containing aluminum alloy phase structure in Example 1. In the figure, diffraction peaks of zinc (100), (002), (101), (103) and (112) crystal planes appear at 2θ=35°, 37°, 45°, 65° and 78°. Figure 4 The XRD spectrum of the phase structure of the aluminum-zinc alloy in Example 4 shows diffraction peaks of the (111), (200), (220), and (311) crystal planes of aluminum at 2θ=38°, 45°, 65°, and 79°. It can be seen from the figure that the preparation method provided by the present invention realizes the process of continuous aluminum plating on metal zinc and continuous zinc plating on metal aluminum.
[0042] 2. Corrosion resistance test The original aluminum and the alloy block formed in Example 1 of the same size were placed in a 0.1 mol / L sodium hydroxide solution, and the gas generated by the corrosion reaction was collected by drainage. In one hour, the volume of gas collected for pure aluminum was about 5 ml, while the corresponding value for the alloy was about 0.5 ml. This indicates that the aluminum-zinc alloy obtained by the preparation method provided by the present invention has excellent corrosion resistance, and when used as an anode material for air batteries, the service life of air batteries can be greatly improved.
[0043] In order to further illustrate the difference in corrosion between pure aluminum and aluminum-zinc alloy metals in alkaline solutions, the present invention conducted a corrosion experiment in which the original aluminum and Example 1 were immersed in a 0.2 mol / L sodium hydroxide solution, and the aluminum was taken out and photographed on the 2nd, 4th, and 8th days. Figure 5 As shown in the figure, in this experimental design, aluminum-zinc alloy was electroplated in the center area of the square aluminum sheet, while the pure aluminum phase was retained in the outer layer (composite polymer was formed in the outer layer before electroplating), which more intuitively shows the corrosion of each part. The three samples in the figure are samples from the same batch prepared under the same conditions. Figure 5 It can be seen that the aluminum-zinc alloy phase formed after electroplating exhibits excellent resistance to alkaline corrosion and slows down the hydrogen evolution reaction.
[0044] 3. Aluminum-zinc alloy for metal-air battery performance testing Pure aluminum and the aluminum-zinc alloy obtained in Example 1 were used as anodes, respectively, with a loading of 1.5 mg / cm 2 The manganese dioxide was used as the cathode and 4 mol / L sodium hydroxide solution was used as the electrolyte to assemble an aluminum-air battery. The limit power density was tested. The test results are as follows Figure 6 As shown. Figure 6 It can be seen that the limit power density corresponding to the aluminum-zinc alloy anode is about 97mW / cm 2 However, due to the severe corrosion reaction of pure aluminum, the corresponding limit power density is about 63mW / cm 2 The data show that when the aluminum-zinc alloy prepared by the continuous preparation method provided by the present invention is used as an anode for an air battery, the ultimate power density of the air battery is at least increased by 54% compared with when pure aluminum metal is used as the anode.
[0045] Pure metallic zinc and the aluminum-zinc alloy obtained in Example 4 were used as anodes to assemble zinc-air batteries with a loading of 1.5 mg / cm 2 The manganese dioxide was used as the cathode and 4 mol / L sodium hydroxide solution was used as the electrolyte to test its limiting power density. The test results are as follows Figure 7 As shown. Figure 7 It can be seen that the limit power density corresponding to the aluminum-zinc alloy anode is about 99mW / cm 2 However, due to the severe corrosion reaction of pure zinc metal, the corresponding limit power density is about 77mW / cm 2 The data show that when the aluminum-zinc alloy prepared by the continuous preparation method provided by the present invention is used as an anode for an air battery, the ultimate power density of the air battery is at least increased by 29% compared with when pure zinc metal is used as the anode.
[0046] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A continuously prepared aluminum-zinc alloy for air batteries, characterized in that: The method is prepared by using a metal zinc rod as an anode and a metal aluminum strip as a cathode or a metal aluminum rod as an anode and a metal zinc strip as a cathode in an electrolyte, and regulating the electroplating current and the transmission speed of the metal aluminum strip or the metal zinc strip in a protective atmosphere; the electrolyte is mainly composed of molten aluminum chloride and zinc chloride.
2. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The electrolyte also includes auxiliary components, which include any one or more of molten lithium chloride, potassium chloride and sodium chloride; the molar ratio of the sum of the molar amounts of aluminum chloride and zinc chloride to the auxiliary components is 3-5:0-1.
3. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The electroplating current density is >1 mA / cm 2 .
4. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The transmission rate is >15 cm / h.
5. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The temperature of the electrolyte is ≥150°C.
6. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The electroplating position can be controlled by compounding a polymer on the surface of the metal aluminum strip or the metal zinc strip.
7. The continuously prepared aluminum-zinc alloy for air batteries according to claim 1, characterized in that: The electroplating current is positively correlated with the transmission speed.
8. Use of the continuously prepared aluminum-zinc alloy for air batteries as claimed in any one of claims 1 to 7 as an anode in air batteries.
9. An air battery, characterized in that: The anode is the continuously prepared aluminum-zinc alloy for air batteries as described in any one of claims 1 to 7.
10. A method for continuously preparing an aluminum-zinc alloy for air batteries, characterized in that: In an electrolyte, a metal zinc rod is used as an anode and a metal aluminum strip is used as a cathode, or a metal aluminum rod is used as an anode and a metal zinc strip is used as a cathode. In a protective atmosphere, the electroplating current and the transmission speed of the metal aluminum strip or the metal zinc strip are regulated to continuously prepare the electrolyte; the electrolyte is mainly composed of molten aluminum chloride and zinc chloride.
Citation Information
Patent Citations
Zinc-aluminum-neodymium alloy and fused salt electrolysis preparation method thereof
CN101914706A
A method for preparing metal aluminum and its alloys by molten salt electrodeposition
CN105112963B
Process of producing zinc-aluminium alloy
CN1258755A